Improvement of Silicon Nanotweezers Sensitivity for Mechanical Characterization of Biomolecules Using Closed-Loop Control - Lafitte, Nicolas; Haddab, Yassine; Le Gorrec, Yann; Guillou, Herve; Kumemura, Momoko; Jalabert, Laurent; Collard, Dominique; Fujita, Hiroyuki (IEEE/ASME Transactions on Mechatronics, 2015)
In this paper, we show that closed-loop control can be advantageously used for the characterization of mechanical properties of biomolecules using silicon nanotweezers (SNT). SNT have already been used in open-loop mode for the characterization of mechanical properties of DNA molecules. Up to now, such an approach allows the detection of stiffness variations equivalent to about 15 DNA molecules. Here, it is shown that this resolution is inversely proportional to the resonance frequency of the whole system and that real-time feedback control with state observer can drastically improve the performances of the tweezers used as biosensors. Such improvement is experimentally validated in the case of the manipulation of fibronectin molecules. The results are promising for the accurate characterization of biopolymers such as DNA molecules.